PERBANDINGAN PERBEDAAN KONSENTRASI RAGI TERHADAP MUTU DONAT KENTANG - Atifah, Ghaida Nurin; Purnama, Hanif Syafrian; Nisa, Khodijah Khoirun; Kusnadi, Kusnadi; Peristiwati, Peristiwati (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 10 No 1 (2023): Scientific Journal of Food Technology (Maret)DO - 10.24843/MITP.2023.v10.i01.p12, 2023)
Donuts are processed flour products made from a combination of several ingredients such as wheat flour, sugar, salt, butter, eggs, water, and yeast as a fermentation agent, these ingredients are mixed with potatoes as an additional raw material. The yeast will grow by converting the sugar into carbon dioxide gas and this gaseous-flavored compound is what makes the donuts rise. The method used in this study was an experimental laboratory method to test the effect of different yeast concentrations on the organoleptic characteristics of potato donuts. The three concentrations of yeast used were 1.4% (w/w), 1.8% (w/w), and 2.2% (w/w). Yeast affected all parameters, taste, color, aroma, and texture of the best donuts in the first treatment with a yeast concentration of 1.4% and the highest organoleptic value.